The Hull Strength of Marine Current Turbine Platform - Achmad Baidowi; Irfan Syarif Arief; Lintang Candra (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2018)
Strength analysis of hull structure of marine renewable energy is crucial. The hull structure must be able to whitstand the harsh environmental load such as wave, wind and the weight of the payload and the structure itself. This paper analyzies the structural hull strength of marine current turbine platform. The platform is held by 4 mooring lines in 200 m water depth. The hull material is AISI1050 with yield stress 530MPa, the analysis consist of stress analysis which consider the dynamic motion of the platform due to wave, current, win and mooring line tension. The dynamic motion shows the maximum gravity acceleration is 1.3496G. The gravity acceleration creates additional loads due to weight multiplication of payload and structure. From the dynamic analysis using numerical software, the maximum mooring line tension due to dynamic analysis is 300.74 kN and this tension will creates stress in the moring line connection structure in the platform hull. The maximum stress of the is 126.045Pa, The mooring line tension is the highest loads compared to other factors such as weight. The safety factor of the structure based on the analysis is 4.2 which can be calculated by comparing the yield stress of the hull material and the maximum stress occurred due to dynamic load.